Effects of match location, quality of opposition and match outcome on match running performance in a Portuguese professional football team - Teixeira, José Eduardo (2021)
The aim of this study was to analyze the effects of match location, quality of opposition and match outcome on match running performance according to playing position in a Portuguese professional football team. Twenty-three male professional football players were monitored from eighteen Portuguese Football League matches during the 2019–2020 season. Global positioning system technology (GPS) was used to collect time-motion data. The match running performance was obtained from five playing positions: central defenders (CD), fullbacks (FB), central midfielders (CM), wide midfielders (WM) and forwards (FW). Match running performance was analyzed within specific position and contextual factors using one-way analysis of variance (ANOVA) for repeated measures, standardized (Cohen) differences and smallest worthwhile change. CM and WM players covered significantly greater total distance (F = 15.45, p = 0.000, η2 = 0.334) and average speed (F = 12.79, p < 0.001, η2 = 0.294). WM and FB players covered higher distances at high-speed running (F = 16.93, p = 0.000, η2 = 0.355) and sprinting (F = 13.49; p < 0.001, η2 = 0.305). WM players covered the highest number of accelerations (F = 4.69, p < 0.001, η2 = 0.132) and decelerations (F = 12.21, p < 0.001, η2 = 0.284). The match running performance was influenced by match location (d = 0.06–2.04; CI: −0.42–2.31; SWC = 0.01–1.10), quality of opposition (d = 0.13–2.14; CI: –0.02–2.60; SWC = 0.01–1.55) and match outcome (d = 0.01–2.49; CI: −0.01–2.31; SWC = 0.01–0.35). Contextual factors influenced the match running performance with differential effects between playing positions. This study provides the first report about the contextual influence on match running performance in a Portuguese professional football team. Future research should also integrate tactical and technical key indicators when analyzing the match-related contextual influence on match running performance